Type VI collagen turnover‐related peptides—novel serological biomarkers of muscle mass and anabolic response to loading in young men. Issue 4 (13th August 2013) - Nedergaard, Anders; Sun, Shu; Karsdal, Morten A.; Henriksen, Kim; Kjær, Michael; Lou, Yunyun; He, Yi; Zheng, Qinlong; Suetta, Charlotte
Abstract : Background: Immobilization‐induced loss of muscle mass is a complex phenomenon with several parallels to sarcopenic and cachectic muscle loss. Muscle is a large organ with a protein turnover that is orders of magnitude larger than most other tissues. Thus, we hypothesize that muscle loss and regain is reflected by peptide biomarkers derived from type VI collagen processing released in the circulation. Methods: In order to test this hypothesis, we set out to develop an ELISA assay against an type VI collagen N‐terminal globular domain epitope (IC6) and measured the levels of IC6 and an MMP‐generated degradation fragment of collagen 6, (C6M) in a human immobilization–remobilization study setup with young ( n  = 11) and old ( n  = 9) men. They were subjected to 2 weeks of unilateral lower limb immobilization followed by 4 weeks of remobilization including thrice weekly resistance training, using the contralateral leg as internal controls. Subjects were sampled for strength, quadriceps muscle volume and blood at baseline (PRE), post‐immobilization (2W), and post‐remobilization (4W). Blood were subsequently analyzed for levels of the C6M and IC6 biomarkers. We subsequently tested if there was any correlation between C6M, IC6, or the C6M/IC6 ratio and muscle mass or strength at baseline. We also tested whether there was any relation between these biomarkers and changes in muscle mass or strength with immobilization or remobilization. Results: The model produced significant loss of muscle mass and strength in the immobilized leg. This loss was bigger in young subjects than in elderly, but whereas the young recovered almost fully, the elderly had limited regrowth of muscle. We found a significant correlation between IC6 and muscle mass at baseline in young subjects ( R 2  = 0.6563, p  = 0.0045), but none in the elderly. We also found a significant correlation between C6M measured at the 4W time point and the change in muscle mass during remobilization, again only manifesting in the young men( R 2  = 0.6523, p  = 0.0085). This discrepancy between the young and the elderly may be caused in part by much smaller changes in muscle mass in the elderly and partly by the relative small sample size. Conclusion: While we cannot rule out the possibility that these biomarkers in part stem from other tissues, our results strongly indicate that these markers represent novel biomarkers of muscle mass or change in muscle mass in young men. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐013‐0114‐x) contains supplementary material.